Analisis Usaha Alat Tangkap Jaring Insang Hanyut (Drift Gill Net) di Desa Pasar Terandam Kecamatan Barus Kabupaten Tapanuli Tengah Provinsi Sumatera Utara - Aprina Siagian; Hendrik; Tince Sofyani (Jurusan Sosial Ekonomi Perikanan, 2020)
This study aimsed to analyze the production and income of the fishing with drift gillnet business, analyze the amount of investment in the fishing with drift gillnet business, and analyze the feasibility of the drift gillnet fishing gear business. The method used in this study is a survey method that is analyzed descriptively. The number of respondents in this study were 30 people. Based on the research results, the total investment for the gill net drift fishing gear business with a fishing fleet of 3 GT size is IDR. 112.042.359. The income (Gross Income) is IDR. 228.525.000 per year of catching and the profit obtained by the fisherman of the drift gill net is IDR. 87.099.790 per year. Based on the calculation of Revenue Cost of Ratio (RCR) investment criteria, a value of 1.62 means that RCR> 1 and the gill drift fishing gear business are profitable and feasible to proceed. Whereas the Financial Rate of Return (FRR) of this drift net fishing gear business is 77.98% and is greater than the current bank deposit interest rate of 6.3%, which means it is better to invest in the business at this time. The Payback Period of Capital (PPC) value is 1.29, meaning that investments in this business can be returned for 198 fishing trips.